2021
DOI: 10.3389/fmed.2021.690995
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Healing Effectiveness and Safety of Anaprazole, a Novel PPI, vs. Rabeprazole in Patients With Duodenal Ulcers: A Randomized Double-Blinded Multicenter Phase II Clinical Trial

Abstract: Background: Proton pump inhibitors (PPIs) are validated gastric acid suppressors and have been widely used to treat patients with active duodenal ulcers. Although existing PPIs have shown great efficacy, many scientists are still devoted to developing more effective PPIs with better safety profile. Herein, we aimed to compare the safety and efficacy of anaprazole in duodenal mucosal healing, a novel PPI, to that of rabeprazole.Methods: In this multicenter, randomized, positive-controlled, double-blinded, paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Although anaprazole was effective at promoting ulcer healing, neither of the doses tested surpassed the clinical efficacy of rabeprazole [28 ▪▪ ]. However, in both dosage groups, there was a potential for better liver tolerance compared with rabeprazole, and therefore, the drug was advanced to phase III clinical trials [28 ▪▪ ]. The potassium competitive acid blocker (P-CAB), vonoprazan fumarate (Takeda Pharmaceutical Company, Tokyo, Japan), was also shown to be as effective at healing duodenal ulcers as the PPI lansoprazole in the setting of H. pylori infection [29 ▪ ], thus expanding available therapeutics for acid-induced duodenal ulceration.…”
Section: Persistent (Deep) Injury and Mucosal Regenerationmentioning
confidence: 81%
See 1 more Smart Citation
“…Although anaprazole was effective at promoting ulcer healing, neither of the doses tested surpassed the clinical efficacy of rabeprazole [28 ▪▪ ]. However, in both dosage groups, there was a potential for better liver tolerance compared with rabeprazole, and therefore, the drug was advanced to phase III clinical trials [28 ▪▪ ]. The potassium competitive acid blocker (P-CAB), vonoprazan fumarate (Takeda Pharmaceutical Company, Tokyo, Japan), was also shown to be as effective at healing duodenal ulcers as the PPI lansoprazole in the setting of H. pylori infection [29 ▪ ], thus expanding available therapeutics for acid-induced duodenal ulceration.…”
Section: Persistent (Deep) Injury and Mucosal Regenerationmentioning
confidence: 81%
“…For active duodenal ulcers, a novel PPI, anaprazole (Sihuan Pharmaceutical Holdings Group, China), was developed with the aim to provide better protection and a better safety profile compared with rabeprazole (AcipHex), which promotes ulcer healing and symptom relief, and has greater acid-blocking profile compared with other PPIs [28 ▪▪ ]. Although anaprazole was effective at promoting ulcer healing, neither of the doses tested surpassed the clinical efficacy of rabeprazole [28 ▪▪ ]. However, in both dosage groups, there was a potential for better liver tolerance compared with rabeprazole, and therefore, the drug was advanced to phase III clinical trials [28 ▪▪ ].…”
Section: Persistent (Deep) Injury and Mucosal Regenerationmentioning
confidence: 99%
“…To reduce bias and control trial quality, the primary endpoint was evaluated by BICR as conducted in both phase II and phase III studies [11] . These phase III findings build on those of the phase II trial that assessed 4-week ulcer healing rates of anaprazole or rabeprazole treatment by BICR [11] . The difference in the ulcer healing rate (−2.8%; 95% CI: −7.7%, 2.2%) was similar to that of the phase II study (−2.9%), confirming the findings of the phase II study in a larger patient population.…”
Section: Discussionmentioning
confidence: 99%
“…In total, the contribution of 2C19 was only 3.5%. Preclinical and phase I studies have shown that anaprazole has an equivalent half-life and pharmacodynamic profile, and an improved safety profile, compared with rabeprazole [11,12] . Patients treated with 10 mg or 20 mg rabeprazole experience high rates of ulcer healing and clinical symptom relief [13,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation